Honeycomb-shaped carbon nanotube supports for BiVO4 based solar water splitting. Issue 47 (25th November 2019) - Jessl, Sarah; Rongé, Jan; Copic, Davor; Jones, Michael A.; Martens, Johan; De Volder, Michael
Abstract : Advances in the synthesis and assembly of nanomaterials offer a unique opportunity to purposefully design nanoparticle structures for a specific applications. Here 3D carbon nanotube structures are coated with BiVO4 for solar water splitting. Abstract : Advances in the synthesis and assembly of nanomaterials offer a unique opportunity to purposefully design structures according to the requirements of the targeted applications. This paper shows a process to create robust 3D carbon nanotube (CNT) structures, which provide an electrically conductive support for nanoparticle coating. We describe a process to reliably fabricate robust honeycomb structures with walls made out of aligned CNTs. We present a design of experimental analysis of this fabrication process and discuss methods to coat these honeycombs with BiVO4 for solar fuel applications. The proposed honeycomb structure allows for an efficient transport of electrons through the electrode, as well as an enhanced light-electrode interaction. Finally, we demonstrate that the developed CNT electrodes can survive harsh BiVO4 synthesis conditions and can subsequently be used as photoelectrodes for solar water splitting.